Somatic Embryogenesis and Direct Shoot Bud Formation from in vitro Root Segments of Garlic (Allium sativum L.) (Plant Tissue Culture and Biotechnology, 2023)
In vitro techniques are unconventionally used for garlic improvement. In garlic tissue culture, numerous roots are produced in vitro. Segments (1 cm) of those in vitro roots were cultivated on MS medium with 5.0 μM 2, 4-D for callus initiation followed by transfer to 0.5 μM 2, 4-D for somatic embryogenesis. Root segments had 51.67% callus and somatic embryo formation. Plantlet regeneration was obtained from 90% calli after being transferred to MS medium supplemented with 5.0 μM kinetin. Within 6 months, 54.8 plants per root segment and 42.2 plants per root tip explant were found. MS media supplemented with 1.0 or 5.0 μM NAA in combination with 10.0 or 50.0 μM BA were used for direct shoot bud induction from root segments. The highest percentage (23.33 %) of direct shoot bud regeneration was found in 5.0 μM NAA with 50.0 μM BA within 2 months. The number of shoots per explant was varied from 1-81 with the highest average of 15.75 shoots per explant. The shoots produced bulblets upon transfer to a medium containing higher amount of sucrose (12%). The largest bulblets weighed 356.57 g in the medium with 5.0 μM NAA and 50.0 μM BA. In both pathways, regeneration occurred from only the apical (distal) end of the root segments. The protocols are promising for continuous regeneration of propagules and genetic transformation study for improvement of garlic.Plant Tissue Cult. & Biotech. 33(2): 135-142, 2023 (December)